Cation exchanged MOF-derived nitrogen-doped porous carbons for CO2 capture and supercapacitor electrode materials. Issue 20 (6th April 2017) - Pan, Ying; Zhao, Yuxin; Mu, Shanjun; Wang, Yu; Jiang, Chunming; Liu, Quanzhen; Fang, Qianrong; Xue, Ming; Qiu, Shilun
Abstract : N-Doped hierarchical porous carbons with enhanced microporosity were prepared by in situ introduction of active site K + into MOF precursors. Abstract : A new strategy was developed to introduce active site K + into the pores of MOF precursors, and various N-doped hierarchical porous carbons were prepared in a one-step synthetic route. The effect of K + in situ activation on the textural properties of the derived porous carbons was studied systematically, and the CO2 capture properties and electrochemical performance of these porous carbons were enhanced for their application in supercapacitors. The KBM-700 sample derived from K@bio-MOF-1 (potassium-ion-exchanged bio-MOF-1), which had high nitrogen content (10.16%) and micropore volume (73%), exhibited good CO2 uptakes (4.75 mmol g −1 ), and high adsorption selectivity for CO2 /N2 at 298 K and 1 bar ( S ads = 99.1) as well as high specific capacitance (230 F g −1 ) and excellent electrochemical cycling stability (97% retention after cycling 10 000 times).